Enhanced thermoelectric properties of CNT dispersed and Na-doped Bi2Ba2Co2Oy composites. Issue 7 (May 2017) - Gao, Wenxian; Chai, Huadou; Wu, Fang; Li, Xinjian; Hu, Xing; Song, Hongzhong
Abstract: The thermoelectric properties of Bi2 Ba2 Co2 Oy and Bi1.975 Na0.025 Ba2 Co2 Oy +x wt% carbon nanotubes (CNT; x=0.00, 0.05, 0.10, 0.15, 0.5, and 1.0) ceramic samples synthesised by the solid-state reaction method were investigated from 300K to 950K. Na doping with a small amount played an important role in reducing resistivity and slightly reduced the Seebeck coefficients and the thermal conductivity. The CNT dispersant increased resistivity, but the thermal conductivity was reduced remarkably. In particular, the Bi1.975 Na0.025 Ba2 Co2 Oy +1.0wt% CNT sample exhibited an ultralow thermal conductivity of 0.39 W K −1 m −1 at 923K. This was attributed to the point defects caused by Na doping and the interface scattering caused by the CNT dispersant. The combination of Na doping and CNT dispersion had better effects on thermoelectric properties. The Bi1.975 Na0.025 Ba2 Co2 Oy +0.5wt% CNT sample exhibited a better dimensionless figure of merit ( ZT ) value of 0.2 at 923K, which was improved by 78.2%, compared with the undoped Bi2 Ba2 Co2 Oy sample.